Family-focused treatment for children and adolescents with bipolar disorder. - Miklowitz, D (2012)
The course of bipolar disorder in children and adolescents is highly recurrent and impairing. This article describes the adaptation of family-focused treatment (FFT) for children and adolescents with bipolar disorder. FFT is given in 21 sessions over 9 months, and is usually initiated during the recovery period following an acute episode of depression or (hypo)mania. The treatment consists of an engagement phase followed by psychoeducation, communication enhancement training, and problem-solving skills training. Results of randomized trials in adults and adolescents find that patients with bipolar disorder who receive FFT and pharmacotherapy recover from episodes more quickly and have longer periods of sustained remission than patients who receive briefer forms of therapy and pharmacotherapy. The application of FFT to youth who are genetically at risk for bipolar disorder is described. Problems in disseminating empirically supported family interventions in community settings are discussed.